2011
DOI: 10.1007/s12206-011-0514-9
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of fluid-structure interaction in a stirred vessel equipped with an anchor impeller

Abstract: A coupling algorithm is used to compute the equilibrium of a flexible anchor impeller in a stirred vessel. This coupling algorithm is based on a partitioned approach, which consists of three relatively independent modules: the computational fluid dynamics (CFD), the computational structure dynamics (CSD) and the interface. In the CFD module, the Euler formulation was used to account for the moving boundary. In the CSD module, the updated Lagrangian formulation for solving the motion of non-linear structure was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This solver makes use of the Updated Lagrangian technique (Karray et al, 2011;Tuković and Jasak, 2007;Pita and Felicelli, 2010), wherein the updated displacements are solved for in the current configuration and the previous time step is used as the reference configuration. To represent the momentum equation in the updated Lagrangian formulation, Eq.…”
Section: Solid Domainmentioning
confidence: 99%
“…This solver makes use of the Updated Lagrangian technique (Karray et al, 2011;Tuković and Jasak, 2007;Pita and Felicelli, 2010), wherein the updated displacements are solved for in the current configuration and the previous time step is used as the reference configuration. To represent the momentum equation in the updated Lagrangian formulation, Eq.…”
Section: Solid Domainmentioning
confidence: 99%
“…Karray et al [22] analyzed the flow-solid coupling behavior of a flexible anchor agitator and found that the fluid has an important influence on flexible paddle deformation. Campbell and Paterson [23] studied the flow-solid coupling motion behavior in flexible turbines and observed that the deformation of flexible paddles could induce the coupling movement of flow and impeller paddles.…”
Section: Introductionmentioning
confidence: 99%
“…Stirring vessels are devices that find extensive applications particularly in chemical, food and biological process industries. Nowadays, numerical simulations are completed with experimental study to construct a better knowledge about the flow characteristics in a stirred vessel [1][2][3][4][5][6][7][8]. Various methods and techniques may be employed when achieving experimental study.…”
Section: Introductionmentioning
confidence: 99%